2022
DOI: 10.3389/fpls.2022.984410
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid accumulation in hemp depends on ROS generation and interlinked with morpho-physiological acclimation and plasticity under indoor LED environment

Abstract: Manipulation of growth and development of cannabis (Cannabis sativa L.) has received considerable interest by the scientific community due to its high value in medicinal and recreational use worldwide. This study was conducted to investigate the effects of LED spectral changes on reactive oxygen species (ROS) and cannabinoid accumulation by provoking growth, pigmentation, photosynthesis, and secondary metabolites production of cannabis grown in an indoor environment. After three weeks of vegetative growth unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 66 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…Total cannabinoid concentrations were unaffected by spectrum and PPFD. These observations contradict with those of Islam et al (2022), who reported increased cannabinoid concentrations under spectra with an increased blue-to-red ratio at a PPFD of 300 μmol m -2 s -1 . Furthermore, in Mentha spp., Sabzalian et al (2014) reported that a combination of red and blue light led to increased essential oil concentrations compared to white light.…”
Section: Discussioncontrasting
confidence: 99%
“…Total cannabinoid concentrations were unaffected by spectrum and PPFD. These observations contradict with those of Islam et al (2022), who reported increased cannabinoid concentrations under spectra with an increased blue-to-red ratio at a PPFD of 300 μmol m -2 s -1 . Furthermore, in Mentha spp., Sabzalian et al (2014) reported that a combination of red and blue light led to increased essential oil concentrations compared to white light.…”
Section: Discussioncontrasting
confidence: 99%
“…When the red and blue spectra were combined, the photosynthetic pigment was greatly increased compared to other spectrum combinations [ 32 ]. In addition, a higher percentage of green with red and blue LEDs has evidence of more chlorophyll accumulation [ 47 ]. According to a previous study, the LED light treatment with red + blue + far-red had a positive influence on the chlorophyll content [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The adaptation of crops to a fragile ecosystem like the haor wetlands in the face of climate change adversities requires resilient varieties, suitable cropping patterns, appropriate irrigation techniques, and sustainable land management. Under stressful conditions, plants should possess the capacity to induce morphological, biochemical, and genetic changes [40,41]. Furthermore, certain modern techniques, like the application of biostimulants or hormones, and cultural practices can enhance the ability of plants to adapt to and cope with adverse situations [42,43].…”
Section: Cropsmentioning
confidence: 99%